2005
DOI: 10.1055/s-2005-925525
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniaeandMycoplasma pneumoniae

Abstract: Mycoplasma pneumoniae infection occurs worldwide and is the most common cause of community-acquired pneumonia (CAP) in 5- to 20-year-olds. The most reliable diagnostic test is the enzyme immunoassay, which allows immunoglobulin (Ig)G and IgM titration and presents 92% sensitivity and 95% specificity on paired samples. Potentially active drugs are tetracyclines, macrolides, ketolides, lincosamides, streptogamines, chloramphenicol, and fluoroquinolones. Chlamydia pneumoniae accounts for 6 to 20% of CAP cases, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…lungs, kidney, liver, etc.) . Mycoplasma pneumoniae releases multiple metabolic products that work as damage‐associated molecular patterns (DAMP), interacting with toll‐like receptors and generating activators of the innate immune system, evidenced by high levels of pro‐inflammatory cytokines such as IL‐6, IL‐18, etc.…”
Section: Mechanisms Of Cardiac Damage During Capmentioning
confidence: 99%
“…lungs, kidney, liver, etc.) . Mycoplasma pneumoniae releases multiple metabolic products that work as damage‐associated molecular patterns (DAMP), interacting with toll‐like receptors and generating activators of the innate immune system, evidenced by high levels of pro‐inflammatory cytokines such as IL‐6, IL‐18, etc.…”
Section: Mechanisms Of Cardiac Damage During Capmentioning
confidence: 99%
“…Mycoplasma pneumoniae, an etiology of atypical pneumonia, has the capability of reaching the heart and triggering pericarditis as well as myopericarditis in adults and children with pneumonia. 56 On the other hand, there is evidence that Chlamydophila pneumoniae is capable of infecting arteriosclerotic plaques, generating an inflammatory reaction inside the arterial vessel that could lead to ACS. 56,57 Using these data, clinical researchers attempted to use macrolides in patients with pneumonia to prevent ACS during CAP, but the study showed the opposite by increasing the number of adverse cardiac events.…”
Section: Mechanisms Of Cardiovascular Complicationsmentioning
confidence: 99%
“…56 On the other hand, there is evidence that Chlamydophila pneumoniae is capable of infecting arteriosclerotic plaques, generating an inflammatory reaction inside the arterial vessel that could lead to ACS. 56,57 Using these data, clinical researchers attempted to use macrolides in patients with pneumonia to prevent ACS during CAP, but the study showed the opposite by increasing the number of adverse cardiac events. 58 Finally, influenza virus was found in the heart of patients who died after influenza B infection (with and without bacterial coinfection) along with evidence of complement activation 59 ; what has opened the possibility that this pathogen could affect the heart during pneumonia as well.…”
Section: Mechanisms Of Cardiovascular Complicationsmentioning
confidence: 99%
“…Chlamydia pneumoniae is an important respiratory pathogen in humans [ 1 ]. Extra-respiratory spread may be common and with consequence: C. pneumoniae or chlamydial DNA has been detected in the coronary arteries of 46% of individuals with atherosclerosis, but rarely in individuals without coronary artery disease [ 2 ].…”
Section: Rationale and Hypothesismentioning
confidence: 99%